(untitled) (Castilla. Estudios de Literatura, 2022)
The fascination that certain poets of the Generación del 36, José Antonio Muñoz Rojas (1909-2009) among them, held for certain figures of the Siglo de Oro, such as Juan de Jaúregui, Francisco de Rioja and Pedro Soto de Rojas, has prompted us to make a analysis of the importance attention given by Muñoz Rojas to the work of 17th century fellow poet Pedro Espinosa (1570-1650), also from Antequera. Such importance is evident in the work that he produced, mainly as a literature researcher and critic in the nineteen-fifties, but also in his own work as an author. Therefore, we analyze the poetic influences of Espinosa in Las cosas del campo, a work written between 1946 and 1947, during Muñoz Rojas’ last years in Andalusia before he took up residence in Madrid at the outset of the fifties. Furthermore, and specifically, we make an in-depth study of the parallelisms we find: insofar as the treatment afforded to Nature and certain features of style.